Gamification im DaF-Unterricht - Miletić, Nikolina (Vestnik za tuje jezike, 2025)
Digital media have fundamentally transformed nearly all areas of modern life. In the field of education, they have brought about a profound shift by making learning more accessible, engaging, and flexible (cf. Niedermeier & Müller, 2016; Pihkala-Posti, 2015; Roche & Suner, 2017). The concept of gamification refers to the use of game mechanics in ed-ucational contexts with the aim of motivating learners to carry out specific actions in the real world. Games can be used in foreign language teaching to promote a learner-centred environment that encourages both active participation and teamwork. The wide range of possible applications takes into account different learning styles and interests. In the world of play, learners can explore and experiment with content according to their own preferences. In doing so, they can develop their skills and creativity, as well as reflect on learning objectives and the entire learning process.This article explores the possibilities for using the self-created Actionbound Alt-stadt-Abenteuer: Zadar durch die Zeiten in the context of teaching German as a foreign language to promote language competencies as well as methodological and didactic prin-ciples in foreign language instruction. The goal was to enable action-oriented and authen-tic learning through a playful city tour in Zadar. A survey was conducted to analyse the effects on foreign language acquisition and on students’ attitudes. The participants were first-year undergraduate and first-year master’s students of German studies at the University of Zadar. The results indicate that the gamification approach is perceived as highly motivating for language learning. Its implementation supports the development of both receptive and productive skills within an authentic learning context. According to the students, digital media can be used in foreign language teaching to create learner-activating and authentic tasks. Since such activities have rarely been integrated so far, they are all the more positively received in foreign language classes.
Keywords: Actionbound; DaF-Unterricht; gamification; Gamification, Actionbound; gamifikacija; GFL instruction; jezikovne spretnosti; language skills; methodisch-didaktische Prinzipien; methodological and didactic principles; metodološka in didaktična načela; pouk nemščine kot tujega jezika; sprachliche Fertigkeiten